Pengaruh Pemberian Kinesiotaping Terhadap Penurunan Nyeri Pergelangan Tangan Pada Pasien Dengan CTS Di RSK Mojowarno Jombang - Binarti Widyanti; Achmad Fariz; Wahyu Teja Kusuma; Sartoyo Sartoyo (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
Objective: CTS is a sensory and motor problem in the hands and fingers that are innervated by the median nerve. The purpose of this research is to determine the effect of kinesiotaping on reducing wrist pain in patients with CTS at Mojowarno Hospital JombangÂ Methods: This study used a quasi-experimental design with a one-group pre-post test design approach, with a total sample of 30 respondents using a purposive sampling technique, and a statistical test using Wilcoxon with a significance level of Î± <0.05.Â Result: From the results of the Wilcoxon statistical test, a significance value (Ï) of 0.000 was obtained, thus H0 was rejected, which means that there was an effect of kinesiotaping on reducing wrist pain in patients with CTS at Mojowarno Hospital, JombangÂ Conclusion : Provision of kinesiotaping therapy is effective in reducing pain that focuses on the wrist as occurs in CTS patients